LTβR-RelB signaling in intestinal epithelial cells protects from chemotherapy-induced mucosal damage - Chen, Qiangxing; Muñoz, Amanda R.; Korchagina, Anna A.; Shou, Yajun; Vallecer, Jensine; Todd, Austin W.; Shein, Sergey A.; Tumanov, Alexei V.; Koroleva, Ekaterina (Frontiers in Immunology, 2024)
The intricate immune mechanisms governing mucosal healing following intestinal damage induced by cytotoxic drugs remain poorly understood. The goal of this study was to investigate the role of lymphotoxin beta receptor (LTβR) signaling in chemotherapy-induced intestinal damage. LTβR deficient mice exhibited heightened body weight loss, exacerbated intestinal pathology, increased proinflammatory cytokine expression, reduced IL-22 expression, and proliferation of intestinal epithelial cells following methotrexate (MTX) treatment. Furthermore, LTβR -/-IL-22 -/-mice succumbed to MTX treatment, suggesting that LTβR-and IL-22-dependent pathways jointly promote mucosal repair. Although both LTβR ligands LIGHT and LTβ were upregulated in the intestine early after MTX treatment, LIGHT -/-mice, but not LTβ -/-mice, displayed exacerbated disease. Further, we revealed the critical role of T cells in mucosal repair as T cell-deficient mice failed to upregulate intestinal LIGHT expression and exhibited increased body weight loss and intestinal pathology. Analysis of mice with conditional inactivation of LTβR revealed that LTβR signaling in intestinal epithelial cells, but not in Lgr5 + intestinal stem cells, macrophages or dendritic cells was critical for mucosal repair. Furthermore, inactivation of the non-canonical NF-kB pathway member RelB in intestinal epithelial cells promoted MTX-induced disease. Based on these results, we propose a model wherein LIGHT produced by T cells activates LTβR-RelB signaling in intestinal epithelial cells to facilitate mucosal repair following chemotherapy treatment.